Controlled Extraction of Flavonoids From Radix Scutellariae by Subcritical Water. Issue 3 (28th December 2015) - Cheng, Yan; Qu, Shaofeng; Wang, Zhenhua; Xue, Fumin; Li, Fuwei
Abstract : The extraction of baicalin, wogonoside, baicalein, and wogonin from Radix Scutellariae was performed using subcritical water and conventional extraction. Compared with ethanol extraction, subcritical water extraction required shorter extraction time, yielded a higher efficiency, and required less extraction solvent. The stability of four flavonoids under subcritical water conditions was investigated, and the extraction products can be controlled through adjusting the properties of subcritical water, namely the selective extraction of some important components. The effects of key operation conditions including extraction temperature (110 to −160 °C), extraction time (10–90 min), water loadings (2.0–4.5 mL), and particle sizes (>20 to <100 mesh) were evaluated. The highest extraction yields of baicalin and wogonoside were obtained at extraction temperature of 12 °C, extraction time of 60 min, water loadings of 4 mL, and 60–100 mesh. The highest extraction yields of baicalein and wogonin were obtained at extraction temperature of 16 °C, extraction time of 20 min, water loadings of 4 mL, and 60–100 mesh. Abstract : It could be shown that subcritical water extraction required a shorter extraction time, yielded a higher efficiency, and required less extraction solvent. Baicalin and wogonoside became unstable at temperatures >130°C, but baicalein and wogonin remained stable at temperatures up to 250 °C. Such flavonoids could be of interest for pharmaceutical and food industries.